2006
DOI: 10.1016/j.bbabio.2006.05.038
|View full text |Cite
|
Sign up to set email alerts
|

A micellar model system for the role of zeaxanthin in the non-photochemical quenching process of photosynthesis—chlorophyll fluorescence quenching by the xanthophylls

Abstract: To get an insight to the mechanism of the zeaxanthin-dependent non-photochemical quenching in photosystem II of photosynthesis, we probed the interaction of some xanthophylls with excited chlorophyll-a by trapping both pigments in micelles of triton X-100. Optimal distribution of pigments among micelles was obtained by proper control of the micelle concentration, using formamide in the reaction mixture, which varies the micellar aggregation number over three orders of magnitude. The optimal reaction mixture wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
1
8
1
Order By: Relevance
“…The absorption spectrum of carotenoids is known to be affected by the interaction of carotenoid molecules with a solvent and by the interaction among the carotenoid molecules themselves [16,[29][30][31][32][33][34][35][36][37][38][39][40][41]. In the present study, the λ max values of carotenoids in the NoPL micelles showed a bathochromic shift compared to those in organic solvents.…”
Section: Discussioncontrasting
confidence: 56%
“…The absorption spectrum of carotenoids is known to be affected by the interaction of carotenoid molecules with a solvent and by the interaction among the carotenoid molecules themselves [16,[29][30][31][32][33][34][35][36][37][38][39][40][41]. In the present study, the λ max values of carotenoids in the NoPL micelles showed a bathochromic shift compared to those in organic solvents.…”
Section: Discussioncontrasting
confidence: 56%
“…It has been postulated that this dimerization may play a role in Zx functioning in the photosynthetic apparatus. 35 It also should be mentioned that some of the recent determinations of the energy levels of the xanthophyll cycle pigments show that the difference between the energies of the S 1 state of Vx and Zx is very small, and therefore essentially different Chl excitation quenching efficiencies for these two compounds may not be expected. 36 Accordingly, no exceptional Chl singlet excitation quenching has been observed in the antenna complexes isolated from the L mutants of Arabidopsis thaliana, in which L was replaced with Zx.…”
Section: Direct Quenching Of Overexcitation By Products Of the Light mentioning
confidence: 99%
“…Micellar systems can also be used as models of thylakoid membranes to investigate the quenching of chlorophyll fl uorescence by xanthophylls such as zeaxanthin or lutein. 51 Micelles of Triton X-100 have been used to trap the pigments chlorophyll and xanthophyll, and CD and fl uorescence measurements showed the aggregation state of the pigments and the non-photochemical quenching effi ciency of chlorophyll fl uorescence by the xanthophylls.…”
Section: Vesicular Model Membranesmentioning
confidence: 99%